Evolvability and Selection in a Tetra-Stranded Genome : Robustness, Modularity, and Adaptive Dynamics in Q-DNA - Barack Ndenga (Publisher, 2025)
Stability and replication are necessary but insufficient conditions for a hereditary polymer to qualify as a biological system. To participate in evolution, a genome must support heritable variation, differential fitness, and adaptive exploration of genotype space. In this work, I investigate the evolvability of Q-DNA, defined as a canonical tetra-stranded hereditary polymer, and analyze the conditions under which tetra-stranded heredity can support evolutionary dynamics. Using fitness landscape arguments and evolutionary simulations at a conceptual level, I show that multi-strand encoding introduces distinctive trade-offs between robustness and innovation, alters mutational neighborhoods, and reshapes adaptive speed. I identify regimes in which Q-DNA favors slow but highly robust evolution, as well as regimes permitting rapid innovation under constrained noise, thereby rendering tetra-stranded heredity evolutionarily viable in principle.
Replication fidelity and structural stability are necessary but insufficient conditions for a hereditary polymer to qualify as a biological system. To participate in Darwinian evolution, a genome must support heritable variation, differential fitness, and sustained adaptive exploration of genotype space. The capacity to evolve—evolvability—is therefore the ultimate test of any proposed genetic architecture. In this work, I investigate the evolvability of Q-DNA, defined as a canonical tetra-stranded hereditary polymer, and analyze the conditions under which tetra-stranded heredity can support evolutionary dynamics. Using fitness landscape arguments and conceptual evolutionary simulations, I show that multi-strand encoding fundamentally reshapes the genotype–phenotype map, introducing strong correlations between mutations and altering the local topology of accessible genotype space. I identify a family of robustness–innovation trade-offs specific to Q-DNA, in which structural redundancy and correlated mutations can buffer deleterious changes while simultaneously constraining or redirecting adaptive exploration. Depending on parameters such as coupling strength, noise level, and decoding rules, Q-DNA systems may favor slow but highly robust evolution, or alternatively enable punctuated bursts of innovation following constraint relaxation. In addition, multi-strand encoding naturally promotes modularity, supporting hierarchical organization and long-term evolutionary persistence. Finally, I formulate falsifiable evolutionary predictions, including excess neutral mutations, episodic adaptation, and enhanced lineage survival under high noise conditions. By treating evolvability as a conditional property emerging from structural and informational constraints, this work establishes selection and adaptive dynamics as the final decisive axis for evaluating Q-DNA as a viable hereditary system and completes a coherent theoretical framework for tetra-stranded genetics within evolutionary theory, synthetic biology, and origin-of-life research.